THE MEANING AND APPLICATION OF INDEPENDENT LEARNING IN THE PERSPECTIVE OF ISLAMIC EDUCATION - Mujib, Abdul; Taher, Zahdi (Pascasarjana IAIN Metro, 2021)
A very interesting issue was discussed when the term